Digitalization Directions within Financial Audit Missions - Dragos Ovidiu TOFAN; Dinu AIRINEI (Audit Financiar)
The current economic dynamics as well as the volatility of the markets or of certain sectors of activity explain the current increasingly pressing need to access complete and updated information on the financial statements of the analyzed organizations. The financial auditor has the necessary expertise to respond to such a desire, but he must rely on new tools dedicated to data processing in order to overcome certain barriers determined by the current information complexity. The paper captures some of the directions of digitalization in carrying out audit missions by revealing advantages and also challenges specific to such innovations. Thus, concrete examples are given, depending on the stages of the financial audit, such as the auditor's own controls or the collection of evidence, processes to which digitalization contributes significantly but also a series of conditions regarding the opportunity, ethics or legal compliance of such technologies.